Pengabdian Kepada Masyarakat KreAtif: Kreativitas Anak Panti untuk Masa Depan Produktif oleh Mahasiswa/i Universitas Muhammadiyah Makassar - Az-Zahra J , Iftitah Resky; Irwani, Irwani; Nadiya Nur Fadilla; Ramadana, Ramadana; Nuryuli, Nuryuli; Ferdinan, Ferdinan (CV. ITTC INDONESIA, 2025)
This Community Service Activity (PKM) “KreArtif” aims to empower orphanage children through the development of creativity and productive skills. The background is the unexplored potential of orphanage children's creativity and the need for provision of independence in the future. The methods used include needs assessment, preparation of training modules, implementation of interactive workshops facilitated by Muhammadiyah Makassar University students, and social entrepreneurship assistance. The expected results are an increase in the capacity of orphanage children in creating valuable works, the growth of entrepreneurial spirit, and increased self-confidence. This program is also expected to strengthen the role of students as agents of social change and foster concern for social issues in society. Thus, “KreArtif” not only focuses on developing creativity, but also on building productive and independent characters for orphanage children, preparing them to become competitive individuals in the future.